COMPARISON BETWEEN TWO METHODS OF METACERCARIAE OF Ascocotyle sp (Trematoda: Digenea) EXTRACTION FROM TISSUES OF Mugil liza Valenciennes, 1836 (Teleostei: Mugilidae) - Renato Ribeiro Nogueira Ferraz; Thales Kodi Namba; Carolina Alencar Nigro; Francisco Sandro Menezes Rodrigues; Anderson Sena Barnabé; João Victor Fornari (Ciência Animal Brasileira, 2014)
The demand and consumption of fish and their derivatives has increased considerably in recent years. However, fish are ideal hosts of numerous parasites, highlighting the need to develop new research methodologies for its detection. The aim of present study was to compare the efficacy of Ascocotyle metacercariae (Trematoda: Digenea) extraction from visceral tissues of Mugil liza Valenciennes, 1836 (Teleostei: Mugilidae) by two methods: homogenization by blender or mixer. Twenty-six samples of M. liza were collected, being 16 liver samples and 10 samples of muscle tissue. Approximately 5g of each sample were processed by blender and mixer techniques homogenization for metacercariae extraction. In liver samples, up to 46 metacercariae were found in samples homogenized in blender. The lowest amount found was 2 metacercariae for blender and mixer techniques. In samples of muscle tissue, 4 metacercariae were observed in the mixer extraction. The lowest amount was found to be 2 parasites to blender and mixer. The mean metacercariae found and extracted from muscle tissue were 0.2 (+0.357) and 1.2 (+0.963) for blender and mixer, respectively. The averages of metacercariae found and extracted from fish liver, in blender and mixer, were 24 (+15.145) and 18 (+8.246), respectively. The homogenization techniques for blender and mixer were effective for the extraction of metacercariae of mullet fish tissues, suggesting that they may be directly applicable in the field of study, especially due to the ease of testing.